ACADEMIC READING PADA PROGRAM MAGISTER FITK UIN SYARIF HIDAYATULLAH JAKARTA - Fahriany, Fahriany (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
The objective of the study is to get comprehemsive understanding of English reading instructional process which can increase English reading competence of Master program Faculty of Tarbiya and teachers training UINÂ  Syarif Hidayatullah Jakarta. The component of instruction consist of : instructional objective, form and function of text, instructional procedure,form and function of instructional activity,the role of student and teacher, and evaluation in reading instruction. This research is a qualitative study, it is done on may 2014, 2013-2014 academic year. The data is collected by using the techniques ofÂ  observation,interview ,and document analysis.The data is analyzed by taxonomy analysis and themes analysis. The result of the study is: English reading instruction in the master program Faculty of Tarbuya and teachers training UIN Syarif Hidayatullah Jakarta runs well .It can facilitate the students develop their reading competence according to their academic needs that is to understand English text which they need in academic situation.The competence can be possed by using many kinds of texts ,applying three reading procedures; pre reading,whilst reading,and post reading.These procedures facilitate the students to be able to use interactive process.